ANALISIS PENGGUNAAN MEDIA KONKRET TERHADAP KEMAMPUAN MATEMATIKA PESERTA DIDIK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR - Zalika Wulandari, Putri; Alexander Alim, Jesi; Hermita, Neni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study aims to determine the impact of concrete mediaon the mathematical abilities of sixth-grade students with special needs at SDN 117 Pekanbaru. The focus of this research is how concrete media can help improve mathematical abilities in the areas of conceptual understanding, problem-solving, reasoning, and mathematical communication. This is a qualitative research using a case study method. Data collection techniques used in this study were observation, interviews, and documentation. Informants concisted of two individuals: a sixth-grades student with special needs identified as a slow learner and the homeroom teacher of the student with special needs. this research was conducted from late July to early August 2025. The results of this study indicate that the use of concrete media has a positive impact on students' mathematical abilities. Concrete media has been shown to facilitate students with special needs in understanding the concept of whole numbers, helping them find problem-solving strategies, developing logical thinking patterns, and improving simple mathematical communication skills.